1999
DOI: 10.1590/s0100-879x1999000300001
|View full text |Cite
|
Sign up to set email alerts
|

[No Title Available]

Abstract: Toxic cyanobacteria are common in Portuguese freshwaters and the most common toxins are microcystins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Desmethyl derivatives have also been reported in Japanese freshwater sources [1], in which methyl groups of N-methyldehydroalanine and N-methyl aspartic acid were replaced by hydrogen atoms. The occurrence of MC-LR has been reported in Portugal since 1990 and a significant number of water reservoirs which are used for drinking water have been reported to have high levels of this toxin [27]. In several studies from Denmark and Slovakia it was shown that MC-LR was the main constituent microcystin in Microcystis blooms, sometimes accompanied by MC-RR, MC-YR or other MCs [61,62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desmethyl derivatives have also been reported in Japanese freshwater sources [1], in which methyl groups of N-methyldehydroalanine and N-methyl aspartic acid were replaced by hydrogen atoms. The occurrence of MC-LR has been reported in Portugal since 1990 and a significant number of water reservoirs which are used for drinking water have been reported to have high levels of this toxin [27]. In several studies from Denmark and Slovakia it was shown that MC-LR was the main constituent microcystin in Microcystis blooms, sometimes accompanied by MC-RR, MC-YR or other MCs [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Some surveys have demonstrated the toxicity of water blooms in several areas of Portugal, including the Douro River and the Guadiana River [2,10,11,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, intoxication can arise via bioaccumulation in food-organisms, mainly fish or mussels from cyanobacterial-contaminated waters [78,108] but also from plants irrigated with cyanobacteria-containing waters [109].…”
Section: Human Fatalitiesmentioning
confidence: 99%
“…Until recently, microcystin intoxication was considered a public health issue mainly of freshwater habitat, reflected by the vast body of published literature on potential human health risks due to microcystin exposure in rivers, lakes, reservoirs and freshwater aquaculture [4], [13], [16], [24], [25], [26]. In contrast, monitoring of marine water and seafood for similar risks has been limited, despite confirmation of outflows of microcystin-contaminated freshwater to the ocean [14], [17], [27], [28], detection of impacts by microcystins on copepods, corals and fish [29][31] and identification of proteins with protein phosphatase inhibitory activity in seawater, suggesting the existence of an additional class of marine “Harmful Algal Blooms” (HAB); hepatotoxic shellfish poisoning (HSP) [15].…”
Section: Introductionmentioning
confidence: 99%